MRI Appearances of Stage IA Ovarian Carcinoma - Cui, Li Wen; Shen, Zhi Yong (Current Medical Imaging, 2024)
ObjectiveTo analyze the MRI findings of stage IA ovarian cancer.MethodsThe data on age distribution, clinical symptoms at onset, CA125 detection, MRI findings, including tumor volume, structure, diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) and enhancement, etc., of the patients with stage IA ovarian cancer, who were admitted to Nantong tumor Hospital between 2013 and 2020 were analyzed retrospectively.ResultsOnly 11 cases of stage IA ovarian cancer were recorded. The age of patients was 30–67 (average 52) years. The initial symptoms were mostly lower abdominal distension and abdominal pain. CA125 was 90% positive. MRI features 1. Large pelvic mass with a volume range of 23–2,009 cm3 (average 669 cm3). 2. Five cases of cyst type (with plaque-like, papillary, or mural nodule vegetations), two cases of cystic-solid mixed type (with thickened septum or wall), and four cases of solid type. 3. DWI diffusion was limited, and ADC was reduced on all solid components (vegetation, septa, and cyst wall). 4. The solid parts were significantly enhanced on T1-enhanced MRI. 5. There was no metastasis in the pelvic cavity, and a few ascites (negative tumor cells) in three patients.ConclusionMRI characteristics of stage IA ovarian carcinomas were large tumors; cystic, cystic-solid, or solid; solid parts limited diffusion on DWI and low ADC; enhancement of the cyst wall, vegetation, and septa; no pelvic metastasis.
Keywords: CA125